Qualitative Analysis and Optimal Control Strategy of an SIR Model with Saturated Incidence and Treatment - Ghosh, Jayanta Kumar; Ghosh, Uttam; Biswas, M. H. A.; Sarkar, Susmita (Differential equations and dynamical systems, 2023)
This paper deals with an SIR model with saturated incidence rate affected by inhibitory effect and saturated treatment function. Two control functions have been used, one for vaccinating the susceptible population and other for the treatment control of infected population. We have analysed the existence and stability of equilibrium points and investigated the transcritical and backward bifurcation. The Pontryagin’s maximum principle has been used to characterize the optimal control whose numerical results show the positive impact of two controls mentioned above for controlling the disease. Efficiency analysis is also done to determine the best control strategy among vaccination and treatment.